Con privilegio: la exclusiva de edición del libro antiguo español. - Reyes Gómez, Fermín de los (Revista General de Información y Documentación, 2001)
Book-privilege, or edition sole rights, is one of the legal figures which most affects the Spanish book market. In addition to appearing in the structure of the book, privilege in many cases implies a printing monopoly of certain books which is detrimental to the interests of a great number of printers and booksellers. This article studies the origin, evolution, characteristics and consequences of this prac tice in the world of Spanish oíd books.
Keywords: Book-privilege; Spanish printing; Spanish oíd books